Gender disparities in all-cause mortality among individuals with early-onset cardiovascular diseases - Jing Yang; Shouling Wu; Yang Liu; Jinguo Jiang; Shuohua Chen; Boheng Zhang; Wei Li; Qi Zhang (BMC Public Health, 2024)
Abstract Background and objective Gender disparities in mortality among individuals with early-onset cardiovascular disease (CVD) remain uncertain. This study aimed to investigate gender differences in all-cause mortality and identify influencing factors. Methods Data extracted from the Kailuan Study, a prospective cohort study initiated in 2006, were analyzed. A total of 2,829 participants with early-onset CVD were included. Cox proportional hazard models were used to assess hazard ratios (HR) and 95% confidence intervals (CI) for gender disparities in all-cause mortality, adjusting for various factors. Results Males experienced a median follow-up duration of 7.54 years with 276 recorded deaths, and females had a median follow-up of 6.45 years with 105 recorded deaths. Gender disparities in all-cause mortality were observed, with men experiencing a higher all-cause mortality risk compared to women (HR: 1.42, 95% CI: 1.04, 1.92) in the fully adjusted model. Both in men and women with early-onset CVD, elevated hs-CRP levels and an eGFR < 60 mL/min/1.73m2 notably escalated the risk of all-cause mortality. Furthermore, the utilization of antiplatelet agents and successful blood glucose control might mitigate the risk of all-cause mortality. Smoking and eGFR decline modified the association between gender and all-cause death, women were more vulnerable to tobacco consumption and kidney misfunctioning than men (P-interaction = 0.019). Conclusion The study highlights gender disparities in all-cause mortality among individuals with early-onset CVD, with men experiencing a higher risk of mortality compared to women. Addressing these disparities is important for improving outcomes in this population. Further research is needed to develop sex-specific interventions and strategies to reduce gender-related mortality disparities in early-onset CVD.